Synchronization of Disaster Financial Policies in COVID-19 Management - Bustami Bustami; Zaky Ulya; Rini Fitriani (Media Syari'ah, 2021)
The COVID-19 outbreak set as a national disaster is one of the steps taken by the government. The government has also ratified the policy of Presidential Decree of the Republic of Indonesia Number 7 of 2020 concerning the Task Force for the Acceleration of Handling Corona Virus Disease 2019 (COVID-19), in addition to supporting the handling of COVID-19, Presidential Regulation of the Republic of Indonesia Number 54 of 2O2O concerning the Posture Changes and Details of State Revenue and Expenditure Budget for Fiscal Year 2O2O. With these two regulations, the government has ordered each region to allocate its regional funds to handle COVID-19. However, the some concerns emerge regarding the budget misuse, reducing the original amount of budget. The method used in this study is a normative juridical method. In this method, theories, concepts, legal principles, laws and regulations related to this research were examined. The results of the study showed that there are too many financial policies set by ministries/institutions to fight against COVID-19, making the local governments confused about how to implement them. Therefore, proper discretion from the local government to allocate the funds until the reporting stage is necessary, so that their implementation will not contradict the existing laws.